PENGALAMAN MAHASISWA DALAM MELAKUKAN WIRAUSAHA INFORMASI: SEBUAH PENELITIAN GROUNDED THEORY - Mahmudah, Afdini; Hariyah, Hariyah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2016)
The main focus of this paper is to explore students’ understanding of information entrepreneurship. This is a qualitative study using grounded theory. Selection of the method is based on research conducted purpose, namely to build a theory based on the views of respondents. The steps taken to obtain the data are interviews, observation, and document review. The data is analyzed based on data analysis model constructivism form of transcription of data and interpretation of data through open coding, axial coding, and selective coding. Because that’s grounded theory meant to know in depth understanding of information entrepreneurship is mainly done by the students. The study also covers entrepreneurship and entrepreneurial activity information extracted information from the perspective of students. The conclusion of this study is an entrepreneur information definition. That defi nition is work in the fi eld of information that can be done independently or in groups, with flexibility in the time and place of the work, in the form of search activity information, creating web and library systems, consulting libraries, teachers, and librarians to make money, add experience and knowledge, as well as develop social activities.